"Is this terrorism?" The Italian media and the Macerata shooting. Issue 4 (2nd October 2022) - Colombo, Monica; Quassoli, Fabio
ABSTRACT: "Media events" and, even more, "contested media events" offer a unique opportunity to analyse how specific interpretative frames come to dominate public debate within a hybrid media system through complex transmedia processes. In this article, we look into how mainstream media and, in particular, daily newspapers, reported on and re-contextualised the fierce debate concerning the "Macerata shooting" that had exploded on Twitter and contributed to obscure the interpretative frame initially proposed by the writer Roberto Saviano, qualifying it as an act of "terrorism". An analysis conducted on a corpus of 143 articles shows that newspapers helped to both spread a mitigated and reassuring picture of the attack, and reaffirm the hegemonic vision of terrorism that sees terrorists, by definition, as alien to the community of victims.